Adaptation for sustainable implementation of Smart Grid in developing countries like Bangladesh. (November 2020) - Maruf, Md Hasan; Haq, Mohammad Asif ul; Dey, Suman Kumar; Al Mansur, Ahmed; Shihavuddin, A.S.M.
Abstract: Smart Grid technology as a platform can encompass several advanced technological features across the spectrum of the power system. Effective Smart Grid system includes smart metering, robust communication infrastructure, deep integration of renewable energy sources, and distributed generation, among other important factors. The presented work in this paper highlights the required adaptation of the potential prime features of Smart Grid technology covering niftier equipment integration and internal cross-platform communication adaptable to the context of Bangladesh. This paper also focuses on the potential cost model for Smart Grid installation in Bangladesh based on the current scenario regarding the power sector. A study on India's Smart Grid that simulates a quasi-similar circumstance helped better comprehend the essential steps required to implement Smart Grids in Bangladesh. Highlights: Five key features for sustainable implementation of Smart Grid have been identified. Current energy and adaptation scenario in Bangladesh have been reported. A novel cost model is proposed based on electrical parameters of an urban region.